App-based self-monitoring as an intervention to support attention in students with learning difficulties - Melzer, Conny; Herwix, Alexander (Frontiers in Education, 2024)
This study examines the effectiveness of an app-based self-monitoring intervention to support attention in students with learning difficulties. Two quantitative single-case studies were conducted in special education school settings. Study 1 used an AB design in which 12 seventh-grade students with learning difficulties were assessed for attentional behavior during a math exercise by systematic observation using the Munich Attention Inventory with five-second time sampling by two raters. Study 2 used a multiple baseline design to assess the attentional behavior of three students with combined learning and attention difficulties during a math exercise by systematic observation using Direct Behavior Rating to measure on-task and off-task behavior. Both studies also used a competency screening to elicit teacher ratings of change in attention behavior in a pre-post measurement. The results indicate that the app-based self-monitoring interventions were successful, highlighting the potential of app-based self-monitoring to support students with learning and attention difficulties. In particular, the development of personalized self-monitoring interventions holds promising potential for improving learning outcomes in this target group.